Prognostic value of cardiac magnetic resonance in elderly patients soon after ST-segment elevation myocardial infarction. (3rd October 2022) - Marcos Garces, V; Gabaldon-Perez, A; Gavara, J; Lopez-Lereu, M P; Monmeneu, J V; Perez, N; Rios-Navarro, C; De Dios, E; Merenciano-Gonzalez, H; Chorro, F J; Valente, F; Lorenzatti, D; et al.
Abstract: Background: Elderly patients with ST-segment elevation myocardial infarction (STEMI) represent a very high-risk population. Data on the prognostic value of cardiac magnetic resonance (CMR) in this scenario are scarce. Purpose: We aim to study the prognostic value of an early (1-week) CMR in elderly patients after STEMI and to create a simple risk score including clinical and CMR variables. Methods: The registry comprised 247 patients over 70 years of age discharged for a first STEMI treated with percutaneous intervention and included in a multicenter registry. Baseline characteristics, echocardiographic parameters and CMR-derived left ventricular ejection fraction (LVEF, %), infarct size (% of left ventricular mass) and microvascular obstruction (MVO, number of segments) were prospectively collected. The additional prognostic power of CMR was assessed using adjusted C-statistic, net reclassification index (NRI) and integrated discrimination improvement index (IDI). Results: During a 4.8-year mean follow-up, 66 (26.7%) first major adverse cardiac events (MACE) occurred (27 all-cause deaths and 39 re-admissions for acute heart failure). Higher GRACE score (HR 1.03 [1.02–1.04], p<0.001), more depressed CMR-LVEF (HR 0.97 [0.95–0.99] per increased %, p=0.006) and more extensive MVO (HR 1.24 [1.09–1.4] per segment, p=0.001) predicted MACE occurrence. The addition of CMR data significantly improved MACE prediction compared to the model with baseline and echocardiographic characteristics (C-statistic 0.759 [0.694–0.824] vs. 0.685 [0.613–0.756], NRI=0.6, IDI=0.08, p<0.001). The best cut-offs for independent variables were GRACE score >155, LVEF <40%, and MVO ≥2 segments. A simple score (0, 1, 2, and 3) based on the number of altered factors accurately predicted the MACE per 100 person-years: 0.78, 5.53, 11.51 and 78.79, respectively (p<0.001). Conclusions: CMR data contribute valuable prognostic information in elderly patients submitted to undergo CMR soon after STEMI. Funding Acknowledgement: Type of funding sources: Public grant(s) – EU funding. Main funding source(s): Instituto de Salud Carlos III and "Fondos Europeos de Desarrollo Regional FEDER" and Conselleria de Educaciόn – Generalitat Valenciana.